New early IAC peach cultivars: Jóia and Doçura types - Ojima, Mário; Dall’Orto, Fernando Antônio Campo; Barbosa, Wilson; Martins, Fernando P.; Santos, Rui R.; Rigitano, Orlando (Pesquisa Agropecuaria Brasileira, 2014)
Jóia-3 (IAC 4974-6), Jóia-4 (IAC 4974-23), Jóia-5 (IAC 976-1) and Doçura-4 (IAC 5174-6) are new dessert peach cultivars, obtained at Instituto Agronômico, Campinas, São Paulo State, Brazil, from crosses between local peach cultivars with peaches and nectarines introduced from Florida, USA. Their main characteristics are great tree vigour, high productiveness, early ripening and white-flesh and freestone fruits. These cultivars are indicated for commercial orchards in the mild winters prevailing in the State of São Paulo, as advantageous alternative to actual cultivars that present similar characteristics.